PENGARUH RELASI, LAYANAN JASA, DAN CITRA PERUSAHAAN TERHADAP KEPUASAN MERCHANT DALAM PENGGUNAAN MESIN EDC DI PT. VISIONET DATA INTERNASIONAL CABANG BEKASI - Idharudin, Vickri; Wahyono, Agus; Noviarti (Jurnal Manajemen, 2025)
This study aims to analyze the influence of Relationships, Service Quality, and Corporate Image on merchant satisfaction in using EDC machines at PT. Visionet Data Internasional, Bekasi Branch. This research employs a quantitative approach, with a survey of a total population of 250 merchants, with 100 samples distributed to merchants using the company's EDC machines. The sampling method used in this study is Purposive sampling, with IBM SPSS (Statistical Product and Service Solutions) as the testing tool. The results show that the variables of Relationships, Service Quality, and Corporate Image have an F value of 25.950, which is greater than the F table value. This indicates that these three independent variables collectively have a significant positive effect on merchant satisfaction. The Relationship variable has a t-value of 3.457, which is greater than the t-table value; Service Quality has a t-value of 3.998, which is greater than the t-table value; and Corporate Image has a t-value of 2.192, which is greater than the t-table value. The conclusion of the t-test shows that the variables of Relationships, Service Quality, and Corporate Image have a partial influence on the satisfaction of merchants using EDC machines from PT. Visionet Data Internasional.